Interacting with virtual instructors: The effect of gender and years of study on the perception of in‐game instructors. (2nd June 2021) - Cui, Dixuan; Whittinghill, David; Fukada, Atsushi; Mousas, Christos; Adamo, Nicoletta
Abstract: Previous research has shown that student‐instructor interaction is vital to motivating students to learn a second language. However, it is unclear whether learners' demographics affect in‐game immersion and interactions with virtual instructors. This study's purpose is to investigate whether the number of years learning Japanese (foreign language familiarity) influences students' immersion levels in serious games and their interactions with virtual instructors. We developed a 3D animated Japanese roleplaying game with a virtual in‐game instructor. Eighty‐four college students enrolled in 200‐ and 300‐level Japanese language courses voluntarily participated in the study. Participants played the game and then answered a questionnaire concerning virtual character appearance, attentiveness to the instructor, and immersion in the game. The findings indicated that gender and the number of years studying Japanese significantly impact multiple measurements. Abstract : This study's purpose is to investigate whether the number of years learning Japanese (foreign language familiarity) influences students' immersion levels in serious games and their interactions with virtual instructors. Participants played a game and then answered a questionnaire concerning virtual character appearance, attentiveness to the instructor, and immersion in the game. The findings indicated that gender and the number of years studying Japanese significantly impact multiple measurements.